Leaching Basalt Rock using Averrhoa Bilimbi Extract - Slamet - Sumardi; Yusup Hendronursito; Kusno Isnugroho; Eka Himmatus Sururiah; Syafriadi Syafriadi; David Candra Birawidha; Muhammad Amin (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2021)
This research was conducted to determine the effect of solid/liquid ratio (s/v), temperature, and stirring Speed on per cent extraction of iron using oxalic acid from Averrhoa bilimbi. The variation of the solid/liquid (s/v) is 10%, 15% and 20 (%), the temperature variations used are 30, 60 and 90 oC, while the variation of the stirring Speed uses 200, 400 and 600 rpm. Some basalt rock samples are put into the reactor and leached using an oxalic acid solution from Averrhoa bilimbi. Within a certain period of time, the filtrate was taken and analyzed for Fe content using Atomic Absorption Spectroscopy. The residue was analyzed using XRF and XRD. The results showed that the highest percentage of iron extraction for basalt rock leaching experiments using oxalic acid from Averrhoa bilimbi was achieved at a temperature of 90oC, 10% of solid/liquid ratio, 400 rpm stirring speed and 120 minutes of leaching time with a percent iron extraction of 65.90%. XRD analysis results showed that the compounds formed in the residual leaching were Anorthite, Ferrosilite, Cristobalite and quart low.